Shopper marketing and the role of in-store marketing - Roggeveen, Anne L.; Nordfält, Jens; Grewal, Dhruv (Emerald, 2014)
This volume of Review of marketing research (RMR) focuses on shopper marketing and the role of in-store marketing. The chapters draw from academic research as well as collaborations with major retailers and industry practitioners. Over the past several decades there has been research into how marketing actions influence how shoppers respond to offers. Yet, with the ever-shifting landscape due to influences such as mobile devices, the internet, and social media, there is an increasing need to understand how marketing actions influence shoppers in their path to purchase. Although there are many path to purchase points which are important to understand, this edition of RMR is devoted to the topic of in-store marketing actions to understand their impact on shopper reactions to offers. The chapters highlight new technologies (e.g., mobile, digital displays) and information aids (e.g., nutrition scores, floor signage) being used by leading retailers to influence the path to purchase. In addition, new research technologies (e.g., eye-tracking, heat maps, in-store experiments) and models that are being used to assess the effectiveness of the path to purchase tactics are discussed.
Keywords: Marketing.; Consumers -- Decision making.; Advertising, Point-of-sale.; elektronické knihy; electronic books